Enhancing crop resilience by harnessing the synergistic effects of biostimulants against abiotic stress - Asif, Anam; Ali, Maratab; Qadir, Muslim; Karthikeyan, Rajmohan; Singh, Zora; Khangura, Ravjit; Di Gioia, Francesco; Ahmed, Zienab F. R. (Frontiers in Plant Science, 2023)
Plants experience constant exposed to diverse abiotic stresses throughout their growth and development stages. Given the burgeoning world population, abiotic stresses pose significant challenges to food and nutritional security. These stresses are complex and influenced by both genetic networks and environmental factors, often resulting in significant crop losses, which can reach as high as fifty percent. To mitigate the effects of abiotic stresses on crops, various strategies rooted in crop improvement and genomics are being explored. In particular, the utilization of biostimulants, including bio-based compounds derived from plants and beneficial microbes, has garnered considerable attention. Biostimulants offer the potential to reduce reliance on artificial chemical agents while enhancing nutritional efficiency and promoting plant growth under abiotic stress condition. Commonly used biostimulants, which are friendly to ecology and human health, encompass inorganic substances (e.g., zinc oxide and silicon) and natural substances (e.g., seaweed extracts, humic substances, chitosan, exudates, and microbes). Notably, prioritizing environmentally friendly biostimulants is crucial to prevent issues such as soil degradation, air and water pollution. In recent years, several studies have explored the biological role of biostimulants in plant production, focusing particularly on their mechanisms of effectiveness in horticulture. In this context, we conducted a comprehensive review of the existing scientific literature to analyze the current status and future research directions concerning the use of various biostimulants, such as plant-based zinc oxide, silicon, selenium and aminobutyric acid, seaweed extracts, humic acids, and chitosan for enhancing abiotic stress tolerance in crop plants. Furthermore, we correlated the molecular modifications induced by these biostimulants with different physiological pathways and assessed their impact on plant performance in response to abiotic stresses, which can provide valuable insights.